Peningkatan Pemahaman Guru Terhadap Media Sosial dalam Pembelajaran - Nurmanita, Tiara Sevi; Cicilia Clara Devi Anggraini (JANACITTA, 2024)
AbstractThe limited use of media makes learning less engaging and can cause students to feel bored. This research aims to examine the utilization of social media to enhance the learning process. Data were collected from statements made by 70 elementary school teachers who responded to a Google Forms questionnaire. The data obtains the grade levels at which teachers teach, the social media platforms, utilization and the impact. The data is processed with Google Forms software in the form of pie charts, while respondents' answers are summarized and processed using a word cloud. The majority of respondents are teachers, teach in grade 1 (28.8%), with only 6.8% teaching in grade 6. The social media platform most commonly used by teachers for teaching was WhatsApp (74.6%), YouTube had the lowest usage (1.7%). Teachers used WhatsApp to send lesson materials (37.3%), assignments (33.9%), video calls (5.1%). WhatsApp was chosen because more efficient and accessible to everyone, including students and the parents. Learning is not confined to the classroom but can also take place on social media outside of school and beyond regular school hours. The limitations of physical space and time for learning are no longer obstacles to the presence of social media.   Abstrak Keterbatasan penggunaan media membuat pembelajaran menjadi kurang menarik dan dapat menyebabkan siswa merasa bosan. Penelitian ini bertujuan untuk mengkaji pemanfaatan media sosial untuk meningkatkan proses pembelajaran. Data dikumpulkan dari pernyataan yang dibuat oleh 70 guru sekolah dasar yang menanggapi kuesioner Google Forms. Data diperoleh dari tingkatan kelas guru mengajar, platform media sosial, pemanfaatan dan dampaknya. Data diolah dengan software Google Forms dalam bentuk pie chart, sedangkan jawaban responden dirangkum dan diolah menggunakan word cloud. Mayoritas responden adalah guru, mengajar di kelas 1 (28,8%), dan hanya 6,8% yang mengajar di kelas 6. Platform media sosial yang paling umum digunakan guru untuk mengajar adalah WhatsApp (74,6%), YouTube memiliki penggunaan terendah (1,7). %). Guru menggunakan WhatsApp untuk mengirimkan materi pelajaran (37,3%), tugas (33,9%), video call (5,1%). WhatsApp dipilih karena lebih efisien dan mudah diakses oleh semua orang, termasuk siswa dan orang tua. Pembelajaran tidak hanya terbatas di dalam kelas saja tetapi juga dapat dilakukan melalui media sosial di luar sekolah dan di luar jam sekolah biasa. Keterbatasan ruang fisik dan waktu belajar tidak lagi menjadi kendala kehadiran media sosial.